Keratin-based bioplastic from chicken feathers - Gupta, Arun; Alashwal, B. Y.; Bala, Md. Saad; Ramakrishnan, N. (Taylor & Francis, 2020)
Chicken feathers are available abundantly as waste, and keratin protein extracted from it can be regenerated into various forms for biotechnological applications, such as films, sponges, fibers, alone or blended with other natural or synthetic polymers. In addition, the chicken feathers consist of about 90% of keratin protein. Based on research, chicken feathers could potentially be used for protein fiber production. Keratin protein is contained in chicken feathers and has some advantages in comparison with other proteins. Rad et al. reported a similar method, but for the removal of impurities, chicken feathers were washed with hot water mixed with detergent for 60 minutes, with the last step repeated twice. The chicken feathers are soaked in ether for 24 hours to remove any oils, grease, or stains. Tensile strengths of keratin based plastics films in this work generally have a lower tensile strength value as compared to other biodegradable plastics, such as starch-based and citric acid cross linked plastics film.